Green PEGylated-Sily@ZnFe2O4 nanocomposites for amelioration of ROS and DNA damage in rat liver - Muhammad Waqas; Muhammad Saqib Saif; Sana Batool; Muhammad Mahmood Ahmed; Tuba Tariq; Riaz Hussain; Ghazala Mustafa; Mansour Ghorbanpour; Murtaza Hasan (Scientific Reports)
Abstract Some conventional drugs are swiftly accessible and poorly soluble in the body. Although it is less soluble and accessible, silymarin, a well-known antioxidant drug, is used to treat several ailments. It is integrated into green-designed Fagonia cretica extract (FCE) based on PEGylated-Sily@ZnFe2O4 in this work to enhance these characteristics. UV–visible spectrometry, X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and zeta potential analysis were all used to thoroughly analyze the nanocomposites. As a result, ZnFe2O4 nanocomposites (NCs) produced nanostructures with an average crystal size of 7.66 nm, whereas PEGylated-Sily@ZnFe2O4 nanodrug produced with an average crystal size of 25.38 nm. The ZnFe2O4 NCs produced nanostructures with an average grain size of 332 nm and 504 nm, respectively as deduce by SEM analysis. Silymarin was estimated to have a loading efficiency of 27.39% into ZnFe2O4 NCs. To examine the produced nano-drug’s in vivo antioxidative capacity in the liver in comparison to pure silymarin, albino rats intoxicated with CCl4 were administered different dosages of 500 and 1500 μg/kg body weight. In hepatic tissue, CCl4 increased ROS and TBARS and lowered SOD, POD, and CAT levels, causing DNA damage that was mitigated subsequently by PEGylated-Sily@ZnFe2O4. In a rat model of CCl4-induced hepatotoxicity, the in vivo assessment experiments showed that the synthesized PEGylated-Sily@ZnFe2O4 efficiently displayed a hepatoprotective effect by mitigating cellular abnormalities caused by CCl4 toxication. Additionally, the PEGylated-Sily@ZnFe2O4 was shown to reduce the degree of DNA damage in the COMET experiment. In contrast to the traditional drug silymarin, the PEGylated-Sily@ZnFe2O4. Nanocomposites may be useful in the future in sustaining a variety of tissues by lowering oxidative stress.